2020
DOI: 10.1101/2020.07.09.20149534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saliva offers a sensitive, specific and non-invasive alternative to upper respiratory swabs for SARS-CoV-2 diagnosis

Abstract: RT-qPCR utilising upper respiratory swabs are the diagnostic gold standard for SARS-CoV-2 despite reported low sensitivity and limited scale up due to global shortages. Saliva is a non-invasive, equipment independent alternative to swabs. We collected 145 paired saliva and nasal/throat (NT) swabs at diagnosis (day 0) and repeated on day 2 and day 7 dependent on inpatient care and day 28 for study follow up. Laboratory cultured virus was used to determine the analytical sensitivity of spiked saliva and swabs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 8 publications
1
41
0
Order By: Relevance
“…One hundred forty-nine papers were considered for inclusion; of these, 19 studies comprising 21 cohorts met inclusion criteria ( Supplemental Figure S1 ). A brief summary of the studies included in this review may be found in Table 1 , and a brief discussion of each paper (including the results used in this review) is presented in the Supplemental Appendix S1 3 , 4 , 5 , 6 , 7 , 8 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 . Twelve of the included cohorts involved 100 or more patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One hundred forty-nine papers were considered for inclusion; of these, 19 studies comprising 21 cohorts met inclusion criteria ( Supplemental Figure S1 ). A brief summary of the studies included in this review may be found in Table 1 , and a brief discussion of each paper (including the results used in this review) is presented in the Supplemental Appendix S1 3 , 4 , 5 , 6 , 7 , 8 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 . Twelve of the included cohorts involved 100 or more patients.…”
Section: Resultsmentioning
confidence: 99%
“…The third study, which was thought to have alow risk of spectrum bias, found saliva to be less sensitive than NP swab 8 . Importantly, 5 of the 7 cohorts in which saliva provided greater sensitivity were thought to be associated with a high risk of spectrum bias with respect to initial diagnostic testing of a community population 21 , 22 , 25 , 27 , 29 . Of 10 cohorts that included patients who had previously tested positive for SARS-CoV2, or included hospitalized patients, four showed higher sensitivity for saliva specimens 21 , 25 , 27 , 29 , two showed sensitivity identical to that for NP swabs 23 , 28 , and four showed higher sensitivity for NP or MT swabs 17 , 18 , 20 , 26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations